Archaeal Hydroxylated Isoprenoid GDGTs in Asian Lake Sediments: A New Tool for Terrestrial Paleotemperature Reconstructions - Jie Wu; Huan Yang; Caiming Shen; Liping Zhu; Yi Yang; Shucheng Xie (Geophysical Research Letters)
Abstract Hydroxylated isoprenoid GDGTs (OH‐GDGTs) have emerged as a novel tool for reconstructing sea surface temperatures. However, when using marine OH‐GDGT calibration in lacustrine settings, it leads to a significant overestimation of temperatures, emphasizing the necessity for a thorough examination of OH‐GDGTs in lakes. Here, we investigated OH‐GDGT distributions in surface sediments from 65 lakes in West China and compiled published Asian lake and global marine OH‐GDGT data sets. Among all GDGT‐based indices, RI‐OH showed the strongest correlation with temperature across Asian lakes. The RI‐OH value was higher in lakes than in marine sediments, likely due to differences in the composition of Group 1.1a thaumarchaeotal species between the two settings. The first RI‐OH temperature calibration for lakes was developed and it addressed the issue of temperature overestimation when applied to both water column and sediment core, highlighting the potential of OH‐GDGTs as a new terrestrial paleothermometer.